Computer Simulation of the Torsion Testing Method with Variable Grip’s Acceleration - Mikhail, Erpalov; Dmitry, Pavlov (KnE Engineering, 2019)
Torsion tests, as well as a number of other test methods, allow to study the rheological properties of various materials, including properties in hot state. However, existing specimen-loading methods as well as methods of experimental data post-processing do not provide obtaining reliable data on the strain resistance of materials sensitive to the strain rate, at high temperatures for example. The article proposes to use the specimen-loading mode with variable grip’s acceleration. This loading mode with the proposed experimental data post-processing algorithm allows to determine the rheological properties of materials that are sensitive to strain rate accurately. In order to verify the new testing method the finite element simulation problem was solved. In Deform-3D software, the process simulation of torsion testing specimens of JIS- NCF718 steel with constant temperature value 982∘C was carried out. The simulation results show that it is possible to determine the strain resistance of materials with the knowledge only of the values of torque and the angle of twist, which are read during the test. Thus, the finite element simulation confirmed the theoretical consistency of the proposed method for testing materials that are sensitive to strain rate. Keywords: hardening curves, strain resistance, torsion test, strain rate sensitivity, finite element simulation